MARITAL OBSTRUCTIONS RESULTING FROM RELIGIOUS TIE - GRĘŹLIKOWSKI, JANUSZ (Prawo Kanoniczne, 2012)
Marital obstructions resulting from religious tie have important and weighty tie have important and weighty place within the range of canonical matrimony law. They make legal reality including two moments: ban of solemnizing the marriage and furthermore the ban of solemnizing marriage under sanction of nullity. Including the double ban, marital obstructions resulting from religious tie belong to the kind if unabling laws, making the person unable for specific legal action. Essence of these obstructions consists in existence of the law, which is not being established freely, but it has its base in the fact or objective circumstance, religious tie resulting from holy orders, public eternal vow of purity and difference of religions, which refer directly to the person solemnizing the matrimony, as well as to the marriage itself. From the obstruction – law, which makes the person unable, the after-effect of “breaking” (nullity) of marriage is born. Legal norms regulating a discipline of obstructions coming from religious tie resulting directly or indirectly from God’s Law, as the unabling law, have in purpose to protect the marital community, institution of marriage and persons solemnizing the matrimony the matrimony. Moreover these norms aim at effective protection of the welfare of the whole Church community in religious, moral and social order. For the church legislator, marriage contract is a public affair, carrying social dimension in it. Hence church society interfere into the sphere of matrimony determining the norms referring to solemnizing the matrimony in situation, where there is an obstruction existing between the betrothed resulting from religious tie. Protection of the welfare of marriage institution, matrimonial community and the betrothed themselves has different degree of application, depending on specific situation of peculiar persons. The welfare of the betrothed being in different life situation forejudges about the possibility for giving a dispensation from described marital obstructions. Dispensation from obstruction of holy orders and public eternal vow of purity made in monastic institution is reserved to the Holy See, whereas dispensation from obstruction of different religious is reserved to bishop ordinary for giving place.